2012
DOI: 10.1021/cb200504g
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Screen for the Engineered Production of β-Lactam Antibiotics

Abstract: High-throughput screens and selections have had profound impact on our ability to engineer proteins possessing new, desired properties. These methods are especially useful when applied to the modification of existing enzymes to create natural and unnatural products. In an advance upon existing methods we developed a high-throughput, genetically-regulated screen for the in vivo production of β-lactam antibiotics using a green fluorescent protein (gfp) reporter. This assay proved reliable, sensitive and presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…As previously reported, Tyr67 was targeted to investigate its possible role as the hydrogen donor involved in epimerization of the (3 S ,5 S )-carbapenam 4 to its C5 epimer 5 . 25 This choice stemmed from inspection of the crystal structure, which showed that a minor shift of less than 2.5 Å by the Tyr67 β-carbon followed by rotation around the α,β-carbon bond would properly position the aryl hydroxyl in the active site for hydrogen donation during the epimerization reaction, thus making it a likely candidate for the proposed radical shuttle required in the coupled reaction of 4 to 6 . Proline 193 was selected to determine if it played a role in positioning the carbonyl of Phe192 to aid in stabilizing and orienting Trp202 for pi-stacking interactions with aromatic residues Tyr191 and Phe194.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, Tyr67 was targeted to investigate its possible role as the hydrogen donor involved in epimerization of the (3 S ,5 S )-carbapenam 4 to its C5 epimer 5 . 25 This choice stemmed from inspection of the crystal structure, which showed that a minor shift of less than 2.5 Å by the Tyr67 β-carbon followed by rotation around the α,β-carbon bond would properly position the aryl hydroxyl in the active site for hydrogen donation during the epimerization reaction, thus making it a likely candidate for the proposed radical shuttle required in the coupled reaction of 4 to 6 . Proline 193 was selected to determine if it played a role in positioning the carbonyl of Phe192 to aid in stabilizing and orienting Trp202 for pi-stacking interactions with aromatic residues Tyr191 and Phe194.…”
Section: Resultsmentioning
confidence: 99%
“…25 The assay has been shown to be acutely sensitive to the presence of β-lactam antibiotics and highly reproducible. Additionally, this assay demonstrated a graded response to β-lactam concentration, which allowed for ranking and comparison of CarC variant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the reactive iron(IV)-oxo species abstracts H• of carbapenam 1 to give a C5-based radical, and subsequently a CarC active site tyrosine (Tyr67) functions as radical donor to donate a H• to the opposite face of the substrate radical to form 2, Fe III -OH and a tyrosyl radical. [27][28][29] Given the imperfection of the initially reported structure, the results of these studies appear to be suspectable. Recently, Chang et al reported a complete crystal structure of CarC in complex with substrate, iron(II), and 2OG with a resolution of 2.10 Å (PDB code: 4OJ8).…”
mentioning
confidence: 88%
“…Computational analyses have supported such a mechanism and involvement of a dedicated H• donor (26). A fluorescence-based in vivo assay for carbapenem production was coupled with amino acid mutagenesis to obtain data suggesting that tyrosine (Y) 67, visualized near the bound N -acetyl-L-proline intended to mimic the substrate in one of two published X-ray crystal structures of CarC, is the H• donor (27, 28). The most recent of these studies employed this structure for molecular-docking analysis that identified a hypothetical substrate-binding mode with C5 in sufficient proximity to Y67 for H• transfer (28).…”
mentioning
confidence: 99%